Lamisil, a potent alternative antifungal drug for otomycosis - Ali Zarei Mahmoudabadi; Zahra Seifi; Maral Gharaghani (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Otomycosis is an acute, subacute or chronic fungal infection of the pinna, the external auditory meatus and the ear canal caused mainly by several species of saprophytic fungi. Lamisil (Terbinafine) is an allylamine antifungal agent, that is used both in the topical and oral administration for the treatment of dermatophytosis, cutaneous candidiasis, and the pityriasis versicolor. We investigated the in vitro activity of clotrimazole, miconazole, nystatin, and Lamisil against the agents of otomycosis. Materials and Methods: Fifteen clinically obtained isolates from otomycosis (Aspergillus species; n=13, and Candida species, n=2) and 8 environmental isolates of Aspergillus were tested. The disk diffusion method was employed to detect susceptibility. In the present study, the in vitro activity of the terbinafine with clotrimazole, miconazole, and nystatin against several isolates of Aspergillus and Candida with different sources were compared. Results: Out of 23 isolates of Aspergillus, Candida 4(17.4%) and 1(4.4%) were resistant to nystatin and miconazole, respectively. In addition, all tested organisms were sensitive to clotrimazole and terbinafine. Statistical analysis has shown that there are no significant differences on the effects of clotrimazole, miconazole and, terbinafine on saprophytic (environmental) and pathogenic isolates of A. niger, A. flavus, and A. terreus (P value= 0.85). In addition, all tested organisms were found to be highly susceptible to terbinafine (P< 0.04). Conclusion: This is a new approach for the possible use of Lamisil for the treatment of otomycosis.